Analysis of Volatile Flavor Compounds of Corn Under Different Treatments by GC-MS and GC-IMS - Zhang, Kangyi; Gao, Lingling; Zhang, Can; Feng, Tao; Zhuang, Haining (Frontiers in Chemistry, 2022)
To establish a rapid and accurate method for detecting volatile components of corn, which will guide the production of corn products fond to consumers. the fingerprints of corns under different treatments including native, washing, blanching, precooling, freezing, steaming, boiling, frying and freeze-drying were depicted via gas chromatography ion mobility spectrometry (GC-IMS) and gas chromatography-mass spectrometry (GC-MS). It was found n-hexanal, 1-octene-3-ol, decylaldehyde and 2-pentylthiazole were speculated to be the key flavor compounds via Venn diagram and relative odor activity value (ROAV). In addition, according to volatile fingerprints characteristics and the aroma profile of sensory evaluation, it was found that corns could be divided into four categories, which was consistent with the results of GC-IMS. And the results of the sensory panel found steamed, boiled and fried corns were much more popular than corns under other treatments with the panel. The results indicated a rapid method to classify products was established by GC-IMS. A suitable processing technology could produce a specific flavor, and further refined research might be focused on finding the best way to process corns.